Assessing the impact of Covid-19 on nurturing care in nairobi slums: Findings from 5 rounds of cross-sectional telephone surveys. - Robert C Hughes; Silas Onyango; Nelson Langat; Ruth Muendo; Rachel Juel; Elizabeth Kimani-Murage; Zelee Hill; Betty Kirkwood; Sunil S Bhopal; Patricia Kitsao-Wekulo (PLOS Global Public Health)
The Covid-19 pandemic and mitigation measures had widespread societal impacts. Young children are particularly vulnerable yet the ways the pandemic affected children in informal settlements (slums) are not well described. This study aimed to investigate the impacts of the pandemic on early childhood in three Nairobi informal settlements. Five rounds of cross-sectional computer assisted telephone surveys (with 578-774 respondents in each) in three settlements (Kibera; Mukuru-Viwandani; Kawangware) over 13 months, correlating with different phases Covid-19 restrictions. Impact was assessed through comparing changes in summary statistics on responses to survey questions on each domain of Nurturing Care over time. Survey results found significant disruptions in healthcare services, particularly in early rounds with missed vaccinations (reported by 1 in 5 parents of infants) and therapeutic healthcare seeking (missed by up to 21% of families). Persistent food and nutrition insecurity, with a large majority of families struggling to feed their children (72% in Round 1) due to financial constraints. Economic shocks were near-universal; 99.7% of respondents reporting earning less since the start of the pandemic. Use of paid childcare initially plummeted but showed a resurgence over time (up to 21% by Round 5) as pandemic control measures evolved. Young children were commonly left alone in all rounds, but especially earlier ones; underscoring the enduring challenges in providing nurturing care in these settings. Very few (<2%) of study participants reported direct experience of illness from Covid-19 in their family in any round. In conclusion, despite adaptations over time and the decrease in reported disruptions, prolonged economic shock was associated with multiple adverse effects on Nurturing Care. The study's longitudinal scope provides insights into the dynamic nature of ensuring young children in slums thrive during crises, highlighting the need for interventions and policies that address the compounded vulnerabilities of young children in these communities.